Urgensi Pemahaman Etika Komunikasi Islami pada Mahasiswa Perguruan Tinggi Agama Islam dalam Mengurangi Dampak Negatif Penggunaan Facebook - Prima Ayu Rizqi Mahanani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
This study aims to see the urgency of understanding the ethics of Islamic communication in an effort to reduce the negative impact that hit Facebook where students of the State Islamic Institute (STAIN) Kediri. Because this situation is contrary to the vision STAIN Kediri who has committed a stabilization center aqidah, good morality, the development of science and a profession that is able to produce graduates who excel intellectually and morally, master of science and technology in order to create a good society. This study used a survey method. The result found that first, many students STAIN Kediri who has not shown good character when a user of Facebook. And secondly, Facebook is used by students STAIN Kediri to argue, in contempt, and a means of contention. An understanding of Islamic ethics of communication required by the students, in order to become the foundation for the user to access Facebook.